2020
DOI: 10.3390/diagnostics10090657
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Recurrent Cervical Cancer and Prediction of Its Patient Survival with Serum Squamous-Cell Carcinoma-Antigen and 2-[18F] Fluoro-2-Deoxy-d-Glucose-Positron Emission Tomography/Computed Tomography

Abstract: Aim: To evaluate the usefulness of serum squamous-cell carcinoma antigen (SCC-Ag) and 2-[18F]fluoro-2-deoxy-D-glucose-positron emission tomography/computed tomography (FDG-PET/CT) for the detection of recurrent squamous-cell carcinoma (SqCC) of the uterine cervix, and its prediction of patient survival. Methods: FDG-PET/CT was performed for patients with serum SCC-Ag levels elevated to ≥1.5 ng/mL (Group 1) and those with suspicious recurrences without any increase in serum SCC-Ag levels (Group 2). The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
(55 reference statements)
1
1
0
1
Order By: Relevance
“…They usually develop local advance and lymphatic spread initially, and by hematogenous dissemination in the late stages. This is supported by the results of several studies investigating 18 F-FDG PET/CT in recurrent cervical cancer, which reported that the most frequent site of recurrence was in lymph nodes [ 13 , 21 , 22 ]. However, cervical neuroendocrine carcinoma exhibits more aggressive behavior and has a different metastatic pattern from cervical cancer with early distal metastases.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…They usually develop local advance and lymphatic spread initially, and by hematogenous dissemination in the late stages. This is supported by the results of several studies investigating 18 F-FDG PET/CT in recurrent cervical cancer, which reported that the most frequent site of recurrence was in lymph nodes [ 13 , 21 , 22 ]. However, cervical neuroendocrine carcinoma exhibits more aggressive behavior and has a different metastatic pattern from cervical cancer with early distal metastases.…”
Section: Discussionsupporting
confidence: 60%
“…18 F-FDG PET/CT has emerged as a useful imaging technique for the detection of recurrent cervical cancer. The reported sensitivity and specificity of 18 F-FDG PET/CT were 93-100% and 59-90.9%, respectively [20,21]. However, the potential of 18 F-FDG PET/CT in recurrent cervical neuroendocrine carcinoma was barely investigated before.…”
Section: Discussionmentioning
confidence: 99%
“…Birincil tedavi başarısız olduğunda, nüks hastalıkta başarı şansı oldukça azdır. Bu nedenle, kanser nüksünün erken tespiti sağ kalım başarısını etkileyebilir 2 . Lokal ileri serviks kanserinin primer tedavisi kemoradyoterapidir.…”
unclassified